Optimization and Modeling of Radial Pitch Diameter Difference in Tapping of AISI H13 - Jie Ren; Tingting Li; Zhi Chen; Yu Meng; Rui Zhang; Xianguo Yan (Advances in Materials Science and Engineering)
The radial pitch diameter difference has a great influence on the quality of the internal thread. However, it is difficult to accurately control the radial pitch diameter difference of the thread in the tapping. Therefore, the influence of various factors on radial pitch diameter difference for tapping AISI H13 steel was studied in this paper. Parameters with optimum radial pitch diameter difference were determined by the Taguchi method, and the tapping experiment was carried out according to Taguchi L18 orthogonal array. Based on the signal-to-noise ratio and variance analysis, the experimental results were evaluated to determine the combination of factors to obtain the smallest radial pitch diameter difference and the influence level of each factor on radial pitch diameter difference, and the prediction equation of radial pitch diameter difference was established through the regression analysis. The results show that the combination of factors to obtain the smallest radial pitch diameter difference is a hone radius of 10 μm, a spindle speed of 100 rev/min, and a chamfer length of 2 pitches; the order of importance of the influencing factors on radial pitch diameter difference is spindle speed, followed by hone radius and chamfer length, and their percentage contribution rates are 61.54%, 24.53%, and 6.16%, respectively; the determination coefficient R2 of the prediction equations is 0.925; the confirmation experiment conducted with 95% confidence level shows that Taguchi method and prediction equation successfully optimize and predict radial pitch diameter difference.